Genome-wide analysis reveals adaptation to high altitudes in Tibetan sheep - Wei, Caihong (Sci Rep, 2016)
Tibetan sheep have lived on the Tibetan Plateau for thousands of years; however, the process and consequences of adaptation to this extreme environment have not been elucidated for important livestock such as sheep. Here, seven sheep breeds, representing both highland and lowland breeds from different areas of China, were genotyped for a genome-wide collection of single-nucleotide polymorphisms (SNPs). The F(ST) and XP-EHH approaches were used to identify regions harbouring local positive selection between these highland and lowland breeds, and 236 genes were identified. We detected selection events spanning genes involved in angiogenesis, energy production and erythropoiesis. In particular, several candidate genes were associated with high-altitude hypoxia, including EPAS1, CRYAA, LONP1, NF1, DPP4, SOD1, PPARG and SOCS2. EPAS1 plays a crucial role in hypoxia adaption; therefore, we investigated the exon sequences of EPAS1 and identified 12 mutations. Analysis of the relationship between blood-related phenotypes and EPAS1 genotypes in additional highland sheep revealed that a homozygous mutation at a relatively conserved site in the EPAS1 3′ untranslated region was associated with increased mean corpuscular haemoglobin concentration and mean corpuscular volume. Taken together, our results provide evidence of the genetic diversity of highland sheep and indicate potential high-altitude hypoxia adaptation mechanisms, including the role of EPAS1 in adaptation.